SISTEM INFORMASI PEMESANAN PRODUK FLORIST BERBASIS WEB PADA QFLORIST - Tiya Alfianti, (2022)
At this time, the field of information and communication technology is experiencing an increasingly rapid revolution. The revolution in information and communication technology has opened up wide opportunities in various fields to solve all problems in their daily lives. Qflorist still uses a manual system that does not support the process of ordering florist products. The manual system without a computerized and integrated system causes the data that has been processed is not well documented, causing errors. Therefore we need a web-based ordering system to facilitate Qflorist in the product ordering process. In making this system using the PIECES method to analyze existing problems, and using UML in the system design process. The system built is web-based and uses codeigniter as a PHP framework, bootstrap as a CSS framework, while for data storage it uses MySQL, for testing the Black Box Testing method is used. With this system, it is expected to simplify the process of ordering products at Qflorist.